2012
DOI: 10.3329/fmcj.v7i1.10296
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations of Chronic Kidney Disease-An Observational Study in 100 Cases

Abstract: Chronic Kidney Disease (CKD) presents with an array of cutaneous manifestations. Newer changes are being described since the advent of haemodialysis, which prolongs the life expectancy, giving time for these changes to manifest. This cross sectional study was performed in 100 cases of CKD admitted in nephrology department of Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU) from April 2008 to August 2008 to evaluate the prevalence of dermatologic problems. Among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
2
10
0
1
Order By: Relevance
“…The incidence of cutaneous manifestations was ranging from 50 to 100% in different studies. [1][2][3][4][5][6][7][8][9][10][11] Uremic pruritus is the most common symptom in our series. Its prevalence varies from 15% to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cutaneous manifestations was ranging from 50 to 100% in different studies. [1][2][3][4][5][6][7][8][9][10][11] Uremic pruritus is the most common symptom in our series. Its prevalence varies from 15% to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Pallor was reported as the hallmark of chronic renal failure. (19) It was observed in 80% of our patients. Udayakumar et al detected pallor in 60% of their patients.…”
Section: Discussionmentioning
confidence: 58%
“…Xerosis was the most common cutaneous abnormality (79%) in the study done by Udayakumar et al among patients on dialysis [7]. Thomas et al [17] and Leena et al [21] also observed xerosis 66.7%…”
Section: Resultsmentioning
confidence: 84%
“…Thomas et al [17] and by Leena et al [21] respectively. Diffuse hyperpigmentation on sun-exposed areas were seen in 33.3% among total CKD patients in this study, which was consistent with these previous studies.…”
Section: Resultsmentioning
confidence: 96%